Surprising diversity of stink bugs (Hemiptera: Pentatomoidea) in a Brazilian ocean beach drift: results of a rapid survey - Limberger, Guilherme M.; Sampaio, Vinicius G.; Brugnera, Ricardo (Entomological Communications, 2023)
The insect drift is a natural phenomenon characterized by the passive movement of insects through air or water currents, which influences their dispersal. The phenomenon of insect drift in ocean beaches represents one of the best-known cases. One of the prominent insect group associated with ocean beach drifts is the Heteroptera, commonly known as true bugs, stink bugs, and water bugs. In this brief communication, we present the diversity of stink bugs (Pentatomoidea) obtained from a rapid survey on an insect drift event at Campeche Beach, Florianópolis, Brazil. The survey was conducted on December 02, 2021, along a transect of 550 meters in the shoreline. A total of 363 individuals were collected. From these, 35 species, 29 genera, and three families were identified. Two species represent undescribed taxa. We found several species that can be considered rare in entomological collections, such as Copeocoris truncaticornis (Stål, 1865) (Hemiptera: Pentatomidae), Capivacius bufo Distant, 1883 (Hemiptera: Pentatomidae), Curatia denticornis Stål, 1864 (Hemiptera: Pentatomidae), and Tibilis subconspersa Stål, 1860 (Hemiptera: Pentatomidae), as well as economically important species such as Diceraeus furcatus (Fabricius, 1775) (Hemiptera: Pentatomidae), Thyanta perdidor (Fabricius, 1794) (Hemiptera: Pentatomidae), and Piezodorus guildinii (Westwood, 1837) (Hemiptera: Pentatomidae). Our results underscore the significance of beach drift events, as they provide valuable opportunities to investigate the hidden diversity within particular taxa, bringing new data while unveiling unknown species. Moreover, the presence of two undescribed species reinforces the importance of researching and documenting drift phenomena for taxonomic purposes, shedding light on insect migration and dispersion patterns.